Organophosphate pesticide trichlorfon induced neurotoxic effects in freshwater silver catfish Rhamdia quelen via disruption of blood-brain barrier: Implications on oxidative status, cell viability and brain neurotransmitters - Baldissera M.D. (2019)
© 2018 Elsevier Inc.The aim of this study was to evaluate whether rupture on blood-brain barrier (BBB) can be a pathway for trichlorfon-induced neurotoxic effects, and to investigate its implications on oxidative status, cell viability and brain neurotransmitters in silver catfish (Rhamdia quelen). The BBB permeability was increased in fish exposed for 24 h to 22 mg/L of trichlorfon compared to the control group, as well as in those exposed to 11 and 22 mg/L of trichlorfon for 48 h. Compared to the control group, brain reactive oxygen species and lipid peroxide levels were higher when exposed to 22 mg/L of trichlorfon and 11 and 22 mg/L of trichlorfon after 24 h and 48 h, respectively, while the antioxidant capacity against peroxyl radical levels was lower. Exposure to 22 mg/L of trichlorfon for 24 h reduced brain cell viability compared to the control group, together with 11 and 22 mg/L of trichlorfon for 48 h. Also, brain AChE, Na+ and K+-ATPase activities were reduced in those fish exposed to trichlorfon compared to the control group. Thus, the rupture of BBB can be considered an important pathway involved in trichlorfon-induced neurotoxic effects, which contributes to brain oxidative damage and important changes on brain neurotransmitters.